Espectro de la flora polinifera de la localidad de El Cano en la provincia ciudad de La Habana - Diaz Milan, M.E.=700 1 Moncada, M.
(Es, En)
Ilus., 6 ref.
Keywords: ABEJA MELIFERA; POLEN; PLANTAS MELIFERAS; IDENTIFICACION; CUBA